Stadium Subsidies, Public Choice, and Property Values: A Test of the Homevoter Hypothesis in King County, Washington. - Miner, Kimberly A. (Tufts Archival Research Center, 2005)
This paper examines the applicability of William Fischel's "homevoter hypothesis" to the 1997 referendum on subsidizing a new stadium for the National Football League's Seattle Seahawks. According to Fischel's hypothesis, homeowners vote for proposals that will increase their property's value and against those that will decrease their property's value. If the homevoter hypothesis explains voter behavior in this instance, then voters who perceive that their home value will increase â via "noisy signals" from sales in their local neighborhood â will be more likely to support the proposal. This paper has two empirical steps: a hedonic analysis to quantify the stadium's impact on property values and an analysis that connects these price effects to voting results in King County, Washington. The results indicate a very small negative stadium price effect, but do not find a strong correlation between this effect and actual voting results. They yield underwhelming support for the homevoter hypothesis but add valuable depth to literature on this topic.